2011
DOI: 10.1016/j.pain.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Statins alleviate experimental nerve injury-induced neuropathic pain

Abstract: The statins are a well-established class of drugs that lower plasma cholesterol levels by inhibiting HMG-CoA (3-hydroxy-3-methyl-glutaryl-coenzyme A) reductase. They are widely used for the treatment of hypercholesterolemia and for the prevention of coronary heart disease. Recent studies suggest that statins have anti-inflammatory effects beyond their lipid-lowering properties. We sought to investigate whether statins could affect neuropathic pain by mediating nerve injury-associated inflammatory responses. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 57 publications
9
52
1
Order By: Relevance
“…Systemic treatment with atorvastatin produced antinociceptive and antihyperalgesic effects in models of bacterial adjuvantinduced inflammatory pain (35) or lipopolysaccharideinduced pain (36). Repeated treatment with simvastatin and rosuvastatin also pro duced an antihyperalgesic effect in mice and rats with nerve injuryinduced neuropathic pain (18). Recently, we also reported that intrathecal, but not intracerebroven tricular, administration of simvastatin exerted an antino ciceptive effect in formalininduced nociception (19).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Systemic treatment with atorvastatin produced antinociceptive and antihyperalgesic effects in models of bacterial adjuvantinduced inflammatory pain (35) or lipopolysaccharideinduced pain (36). Repeated treatment with simvastatin and rosuvastatin also pro duced an antihyperalgesic effect in mice and rats with nerve injuryinduced neuropathic pain (18). Recently, we also reported that intrathecal, but not intracerebroven tricular, administration of simvastatin exerted an antino ciceptive effect in formalininduced nociception (19).…”
Section: Discussionmentioning
confidence: 85%
“…Systemic treatment with the lipidlowering drugs simvastatin and rosuvastatin attenuates thermal hyperal gesia and mechanical allodynia in nerveligated rats (18). We recently reported that intrathecal treatment with simvastatin attenuated the second, but not first, phase of the formalininduced nociceptive response, suggesting inhibition of the sensitization of spinal nociceptive trans mission (19).…”
Section: Introductionmentioning
confidence: 96%
“…Interleukin-1␤ (Scannell, 1996), interleukin-6 (Albina et al, 1995, tumor necrosis factor-␣ (Cramer et al, 2003), and CC chemokine ligand 3 (Bosco et al, 2004) are upregulated in macrophages by hypoxia. These same molecules are upregulated in macrophages in models of neuropathic pain (Shi et al, 2011;Lee and Zhang, 2012;Lim et al, 2014). It is possible that targeting hypoxia may abrogate many unwanted effects of macrophages, without affecting their beneficial functions.…”
Section: Increased Metabolic Needs Contributes To Endoneurial Hypoxiamentioning
confidence: 99%
“…It is reported that systemic treatment with atorvastatin produces antinociceptive and antihyperalgesic effects in inflammatory pain induced by bacterial adjuvant (4) or lipopolysaccharide (5). Repeated treatment with simvastatin and rosuvastatin also produces an antihyperalgesic effect in nerve injury-induced neuropathic pain in mice and rats (6). These reports suggest that these effects of HMG-CoA reductase inhibitors might be mediated by the anti-inflammatory effect.…”
mentioning
confidence: 93%